1991
DOI: 10.1111/j.1464-410x.1991.tb15191.x
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Instillations of Trisdine Compared with Catheter Introducer for Reduction of Bacteriuria during Intermittent Catheterisation of Patients with Acute Spinal Cord Trauma

Abstract: An open, prospective, randomised trial was conducted to compare the incidence of significant bacteriuria following 2 methods of intermittent urethral catheterisation in patients with acute spinal cord trauma. Twenty-two patients were catheterised with a Nelaton catheter and 50 ml of Trisdine were instilled into the bladder and left there immediately prior to withdrawal of the catheter. Fifteen patients were catheterised with a Nelaton catheter with a special introducer to improve asepsis (O'Neil catheter). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Fifteen articles reported the occurrence of UTIs or bacteriuria as a primary outcome. [11][12][13][14]17,20,[23][24][25][26]28,30,36,38,39 The definition of UTI was not consistent and varied from 'clinical infection with symptoms of UTI and for which treatment was prescribed' to '10 5 CFU per ml plus at least one of the following symptoms of fever, pyuria, hematuria, chills, increased spasms or autonomic dysreflexia'. 43 Bacteriuria was more consensual and mostly defined as the identification of one or more 'usual' pathogens in the urine, associated with a colony count of more than 10 4 -10 5 CFU per ml, and absence of symptoms or pyuria.…”
Section: Bacteriuria and Genito-utismentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen articles reported the occurrence of UTIs or bacteriuria as a primary outcome. [11][12][13][14]17,20,[23][24][25][26]28,30,36,38,39 The definition of UTI was not consistent and varied from 'clinical infection with symptoms of UTI and for which treatment was prescribed' to '10 5 CFU per ml plus at least one of the following symptoms of fever, pyuria, hematuria, chills, increased spasms or autonomic dysreflexia'. 43 Bacteriuria was more consensual and mostly defined as the identification of one or more 'usual' pathogens in the urine, associated with a colony count of more than 10 4 -10 5 CFU per ml, and absence of symptoms or pyuria.…”
Section: Bacteriuria and Genito-utismentioning
confidence: 99%
“…Spinu 2012 (NRS) (38) Vapnek 2003 (RCT) (24) De Ridder 2005 (RCT) (25) Pachler 1999 (RCT) (17) Cardenas and Hoffman 2009 (RCT) (36) Bennett 1997 (RCT) (16) Cardenas 2011 (RCT) (30) Fingerhut 1997 (RCT) (14) Charbonneau-Smith 1993 (NRS) (39) Moore 2006 (RCT) (26) Quigley PA 1993 (RCT) (12) Duffy LM 1995 (RCT) (13) Sùrensen 1999 (RCT) (18) Mauroy 2001 (RCT) (20) BIERING-SØRENSEN 2007 (RCT) (29) Costa 2013 (RCT) (33) Chartier-Kastler 2013 (RCT) (34) Chartier-Kastler 2011 (RCT) (31) Domurath 2011 (RCT) (32) Johansen 2007(NRS) (40) Johansson 2013 (RCT) (35) Denys 2012 (NRS) (41) Diokno 1995 (NRS) (42) Fader 2001 (RCT) (21) Pascoe 2001 (RCT) (22) Witjes 2009 (RCT) (37) Wyndaele 2000 (RCT) (19) Ginnantoni 2001 (RCT) (23) Waller 1997 (RCT) (15) PEARMAN 1991(RCT) (11) Sekiguchi et al 2007 (RCT) (28) 0% 20% 40% 60% 80% 100%…”
Section: Other Biasmentioning
confidence: 99%
“…In previous studies, Klebsiella and Pseudomonas were the most frequently isolated organisms in male patients with SCI. [12][13][14][15] However, in our study, E. coli was the most frequently isolated bacteria in both urine and urethral samples. In accordance with the results of other similar studies, we found that E. coli was the most frequently colonized organism in urine and urethra in female patients.…”
Section: Discussionmentioning
confidence: 78%
“…13 Oral antibiotics, methenamine compounds, and bladder instillations of providone iodine and chlorhexidine preparations are often used and have been shown to postpone bacteriuria for short periods in patients managed with CIC. 14,15 Daily use of low-dose systemic antimicrobials such as trimethoprim-sulfamethoxazole has also been shown to be effective in reducing bacteriuria and symptomatic UTI in persons with acute SCI. 7 The routine use of methenamine products or systemic antimicrobials for prophylaxis in long-term intermittent catheterization is controversial and not recommended 16 ; however, in carefully selected subjects with frequent recurrent symptomatic UTIs, this may help improve quality of life.…”
Section: Discussionmentioning
confidence: 99%